2012
DOI: 10.1121/1.4739461
|View full text |Cite
|
Sign up to set email alerts
|

Energy- and wave-based beam-tracing prediction of room-acoustical parameters using different boundary conditions

Abstract: A beam-tracing model was used to study the acoustical responses of three empty, rectangular rooms with different boundary conditions. The model is wave-based (accounting for sound phase) and can be applied to rooms with extended-reaction surfaces that are made of multiple layers of solid, fluid, or poroelastic materials—the acoustical properties of these surfaces are calculated using Biot theory. Three room-acoustical parameters were studied in various room configurations: sound strength, reverberation time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Yousefzadeh and Hodgson compared predictions of energy-and pressurebased coefficients as well, especially from the viewpoint of local and extended reactions. 135 Their main conclusion was that a pressure-based model with extended reaction is needed if the space under study includes multi-layered surfaces.…”
mentioning
confidence: 99%
“…Yousefzadeh and Hodgson compared predictions of energy-and pressurebased coefficients as well, especially from the viewpoint of local and extended reactions. 135 Their main conclusion was that a pressure-based model with extended reaction is needed if the space under study includes multi-layered surfaces.…”
mentioning
confidence: 99%
“…In the area of beam tracing method, some recent works [31][32][33] focused on the influence of boundary conditions on the prediction results. In the work of Siltanen et al [ 34], they presented a way to introduce incoherent reflections in a beam tracer algorithm.…”
Section: Geometrical Acoustical Methodsmentioning
confidence: 99%
“…In such case the extended reaction assumption is preciser and improves the theoretical and experimental agreement of sound pressure level predictions [26]. Moreover, the significance of introducing extended reaction boundaries into computer models has been demonstrated -using phased beam tracing, the influence on the steady state sound pressure level in frequency bands was shown by Hodgson and Wareing [27] and on several acoustic parameters (strength, reverberation time and rapid speech transmission index) by Yousefzadeh and Hodgson [28]. Recently, Yasuda et al [29] showed by wave-based modeling that the extended reaction alters the response in particular at low frequencies, which is also the frequency range of our interest.…”
Section: Introductionmentioning
confidence: 94%